2021
DOI: 10.1021/acs.jpcb.0c11158
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Orientation at the Squalene/Air Interface from Sum Frequency Generation Spectroscopy and Atomistic Modeling

Abstract: Human skin oils are significant scavengers of atmospheric oxidants in occupied indoor environments, and squalene is a major ozone-active constituent. Here, we present a combined spectroscopic and atomistic modeling approach to elucidate the conformational and orientational preferences of squalene at the air/oil interface and their implications for reactions with ozone. We find that squalene chains have a tendency to align with the surface normal, resulting in different concentrations of the various types of it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 73 publications
(131 reference statements)
1
21
0
Order By: Relevance
“…The MD simulations in refs ( 48 ) and ( 49 ) are in agreement with our earlier study 5 that indicated squalene has a relatively extended conformation in nonpolar solutions. The calculations and Figure 4 of ref ( 48 ) showed that ∼94% of 343 molecules were relatively extended; ∼45% had all- anti methylene bridges, ∼37% had one gauche defect, and ∼12% had two. The percentages in bulk squalene and the interface were essentially the same.…”
Section: Discussionsupporting
confidence: 89%
“…The MD simulations in refs ( 48 ) and ( 49 ) are in agreement with our earlier study 5 that indicated squalene has a relatively extended conformation in nonpolar solutions. The calculations and Figure 4 of ref ( 48 ) showed that ∼94% of 343 molecules were relatively extended; ∼45% had all- anti methylene bridges, ∼37% had one gauche defect, and ∼12% had two. The percentages in bulk squalene and the interface were essentially the same.…”
Section: Discussionsupporting
confidence: 89%
“…SFG is a second-order nonlinear optical process characterized by second-order nonlinear optical susceptibility χ (2) . ,,,, SFG theories, experimental setups, and data analyses have been extensively reported ,,,, and will not be repeated here. Under the electric dipole approximation, the SFG signal cannot be generated from most bulk materials which have inversion symmetry but can be produced from surfaces/interfaces where inversion symmetry is broken. ,,,, …”
Section: Methodsmentioning
confidence: 99%
“…A notable indoor ozone reaction is with squalene. Squalene is a 30-carbon chain molecule that contains six trans-oriented carbon–carbon double bonds, accounts for 5%–15% of the total human sebum composition, and accounts for approximately 48% of the unsaturated double bonds in skin oil, which makes it one of the most reactive components in human sebum. The other main components of sebum are fatty acids, wax monoesters, triglycerides, cholesterol, and cholesterol esters. ,, Squalene is a semivolatile unsaturated compound that is continuously produced by the body’s sebaceous glands and is on the surface of the skin, hair, and clothing, as well as in dust as a component of dead skin cells and in indoor particulate matter. ,, In addition, squalene is found in fingerprints, which places squalene on most surfaces around the home. , Sebaceous glands produce squalene to beneficially protect the lower layers of the skin’s structure from oxidation by atmospheric oxidants such as free radicals and ozone . The amount of squalene on one’s skin does not vary significantly throughout the day due to continual reactions and replenishment from the sebaceous glands. , Since the SqOz reaction occurs on people’s skin and clothing that contains squalene while being worn, there is high potential for exposure to the reaction products.…”
Section: Introductionmentioning
confidence: 99%